Microwave dielectric measurement of jowar (Sorghum Vulgare Pers.) at 9.85 GHz frequency - Karhale, G A; Kalamse, G M (International Multidisciplinary Research Journal, 2012)
The effect of packing density and temperature on dielectric parameters, dielectric constant , dielectric loss , loss tangent , relaxation time , conductivity , moisture content of Jowar (Sorghum Vulgare Pers) was assessed.Â The results showed that there was a systematic increase in dielectric constant and loss factor with increasing values of relative packing fraction and decrease in dielectric constant and loss factor with increasing temperature. Moisture content is measured using thermo-gravimetric method. Experimental results of different relative packing fractions (Î´r) were further used to obtain transformation to 100% solid bulk using correlation equations of Landau-Lifshitz-Looyeng and Bottcher.Â There was a good agreement between experimental values and theoretical values of different dielectric parameters. The result shows cohesion in the particles of Jowar powder under investigation.